Regenerative approaches for the cornea. (20th April 2016) - Griffith, M.; Alarcon, E. I.; Brunette, I.
Abstract: The cornea is the transparent front part of the eye that transmits light to the back of the eye to generate vision. Loss of corneal transparency, if irreversible, leads to severe vision loss or blindness. For decades, corneal transplantation using human donor corneas has been the only option for treating corneal blindness. Despite recent improvement in surgical techniques, donor cornea transplantation remains plagued by risks of suboptimal optical results and visual acuity, immune rejection and eventually graft failure. Furthermore, the demand for suitable donor corneas is increasing faster than the number of donors, leaving thousands of curable patients untreated worldwide. Here, we critically review the state of the art of biomaterials for corneal regeneration. However, the lessons learned from the use of the cornea as a disease model will allow for extension of the biomaterials and techniques for regeneration of more complex organs such as the heart. Abstract : Content List – Read more articles from the symposium: Human models and technology for regenerative medicine.